Spontaneous portosystemic shunts in cirrhosis: Detection, implications, and clinical associations. Issue 11 (November 2021) - Rathi, Sahaj; Brocco, Silvia; Formentin, Chiara; Zarantonello, Lisa; Mangini, Chiara; Meneghello, Gianluca; Merkel, Carlo; Angeli, Paolo; Stramare, Roberto; Montagnese, Sara; Amodio, Piero
Abstract: Background: Spontaneous portosystemic shunts (SPSS) are common in cirrhosis. Their characterization and clinical implications remain unclear. Aims: To devise a system of assessment of these shunts, and assess their clinical implications Methods: We retrospectively studied patients with cirrhosis who underwent imaging in a liver transplant program. A novel index was computed to assess total SPSS -the diameter of a circle having an area equivalent to the sum of the areas of all the existing shunts. This 'SPSS equivalent diameter' was compared with the clinical variables. Results: Among 127 patients, 70% (CI95% 62–77) had SPSS, and 57% (CI95% 62–77) had multiple SPSS. The risk for SPSS was related to the severity of cirrhosis (Child-Pugh B/C vs. A: OR 2.4 CI95% 1.1–5.4) and alcoholic aetiology (OR 2.9 CI95% 1.2–7.1). The SPSS equivalent diameter was related to a history of HE, cognitive impairment (EEG/PHES) and ammonia( p <0.05). The diameter of the inferior cava vein >19.5 mm was a predictor of large SPSS (AUC 0.77, CI95% :0.68–0.87, p ≤ 0.001). Conclusions: The SPSS equivalent diameter, a comprehensive assessment of portosystemic shunting, was associated with severity of liver disease, hyperammonemia, and cognitive dysfunction. The diameter of the inferior vena cava was a good predictor of SPSS.